2001
DOI: 10.1144/geochem.1.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Water-quality trends for a stream draining the Southern Anthracite Field, Pennsylvania

Abstract: Stream flow, chemical and biological data for the northern part of Swatara Creek, which drains a 112 km 2 area in the Southern Anthracite Field of eastern Pennsylvania, indicate progressive improvement in water quality since 1959, after which most mines in the watershed had been flooded. Drainage from the flooded mines contributes substantially to base flow in Swatara Creek. Beginning in 1995, a variety of treatment systems and surface reclamation were implemented at some of the abandon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Brennan and Lindsay [58] found that a more prolonged and intensive reduction period was required for the reduction of crystalline oxides (hematite) compared to nearly amorphous iron (hydr)oxides. Younger, freshly precipitated iron has a large (>200 m 2 /g) [38,39,59] and complex surface area [60,61]. Grain size is also a major control on the potential for reduction.…”
Section: Changes In Mineral Form and Mobility Of Trace Metal Contaminmentioning
confidence: 99%
“…Brennan and Lindsay [58] found that a more prolonged and intensive reduction period was required for the reduction of crystalline oxides (hematite) compared to nearly amorphous iron (hydr)oxides. Younger, freshly precipitated iron has a large (>200 m 2 /g) [38,39,59] and complex surface area [60,61]. Grain size is also a major control on the potential for reduction.…”
Section: Changes In Mineral Form and Mobility Of Trace Metal Contaminmentioning
confidence: 99%
“…During 1996-1998, streamwater of Swatara Creek at Newtown and Ravine ( Fig. 1) ranged from mildly acidic to near-neutral (net acidity -20 to 10 mg/L CaCO 3 ; pH 4.5-8.0) with moderate concentrations of dissolved solids (SC 60-400 lS/cm) that varied as a function of stream flow (Cravotta and Bilger 2001;Cravotta and Weitzel 2001). Higher values of pH, SC, and SO 4 were associated with base-flow conditions sustained by near-neutral groundwater and net-alkaline AMD in the upper part of the watershed, such as the Tracy Airshaft and Colket discharges (Fig.…”
Section: Characterization Of Amd Sources and Effects On Streamwater Qmentioning
confidence: 99%
“…Increased transport of iron, the principal pollutant in mine drainage entering Bear Creek, can occur in streams that rapidly respond to storm events through scour of streambed sediments and episodic acidification (Cravotta and Bilger, 2001). Iron and trace metals generally are associated with fine streambed sediments (<0.063-mm size particles), those that are most likely to be entrained and transported during rapid increases in flow.…”
Section: Effects Of Historical Coal Mining On Streamflow 15mentioning
confidence: 99%
“…16), it remained near-neutral (minimum pH = 6.1; table 5) making the dissolution of relatively insoluble Fe(OH) 3 unlikely over the range of measured pH values. Nonetheless, there are processes facilitated by decreases in pH and (or) redox potential of streambed sediments or the water column that may increase the concentrations of dissolved metals (Cravotta and Bilger, 2001). …”
Section: Ironmentioning
confidence: 99%